A Comparative Study of Efficacy and Safety Between Tamsulosin and Terazosin in the Treatment of Symptomatic Benign Prostatic Hyperplasia (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2016)
Background: Lower urinary tract symptoms suggestive of symptomatic Benign Prostatic Hyperplasia (BPH) are a very common disease in elderly men .The incidence of benign prostatic hyperplasia is age related.Objectives: To compare the efficacy and safety of Tamsulosin and Terazosin in the treatment of symptomatic Benign Prostatic Hyperplasia.Methods: This was a prospective study carried out in the Department of Urology, Chittagong Medial College Hospital, Chittagong, Bangladesh during the period of July to December 2014. Total 40 patients of 45-80 years of age were consequently selected according to inclusion criteria. After completion of baseline clinical evaluation and investigations, participants were divided into two groups, group A and group B. Group A (n=20) was given Terazosin 1mg daily for 3 days at bed time and then 2 mg daily at bed time for 2 months. Group B (n=20) was given Tamsulosin, 0.4 mg per day for 2 months. Efficacy was evaluated of each group after 2 month follow up and lastly a comparison was made between them. The parameters monitored were International Prostate Symptoms Score (IPSS) Maximum urine flow rate (Qmax) and Post Voidal Residual Volume (PVR). Tamsulosin 0.4 mg and Terazosin 2 mg once daily for 8 weeks both are effective in relieving symptoms of BPH but Tamsulosin is superior to Terazosin in improvement of total IPSS (p